Jewish-Israeli National Identity and Dissidence - Attwell, K. author. aut Link
XII, 229 p.
Keywords: A critical examination of Zionism and its internal resistance by Israeli Jews, this book employs a unique perspective on Israel/Palestine by eschewing presenting identities as concrete and, rather, examining their creation through discourse.